Method for recovering cathode material from lithium-ion batteries

CN122996209APending Publication Date: 2026-10-27ENI SPA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580017346.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-26
Filing Date
2025-02-25
Publication Date
2026-10-27

Smart Images

  • Figure CN122996209A_ABST
    Figure CN122996209A_ABST
Patent Text Reader

Abstract

Process for the recovery of a cathode material from a lithium-ion battery, comprising the following phases: (a) separation of a cathode from a lithium-ion battery, said cathode comprising a cathode material and a current collector, said cathode material comprising at least one active cathode material, at least one binder and optionally at least one conductive material, said cathode material being adhered to said current collector by means of said at least one binder; (b) contacting said cathode with at least one diol; (c) peeling said cathode material from said current collector, obtaining a mixture comprising a suspension of said cathode material dispersed in a liquid phase comprising said at least one diol and a current collector immersed in said suspension; (d) recovering said cathode material and said current collector from said mixture; characterized in that said phase (c) is carried out in the presence of ultrasound with a power comprised between 30 and 500 Watts, preferably between 50 and 300 Watts, at a temperature comprised between 80 and 280°C, preferably between 85 and 260°C, for a time comprised between 15 minutes and 24 hours, preferably between 30 minutes and 20 hours. From the cathode material recovered by the process described above, after suitable treatments, it is possible to obtain a recovered active cathode material (for example by means of a direct recycling process) or a synthetic precursor that can be used for the regeneration of said active cathode material (for example by means of a hydrometallurgical process), said active cathode material in turn being usable in lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to a method for recovering cathode materials from lithium-ion batteries.

[0002] More specifically, the present invention relates to a method for stripping and recovering cathode material from a lithium-ion battery, the method being carried out in the presence of at least one diol and ultrasound under specific power, temperature and time conditions.

[0003] From the cathode material recovered by the above method, after appropriate processing, recovered active cathode material can be obtained (e.g., through a direct recycling process), or synthetic precursors that can be used to regenerate the active cathode material can be obtained (e.g., through a hydrometallurgical process), which can then be used in lithium-ion batteries.

[0004] In the coming years, lithium-ion battery production will grow exponentially in the automotive industry (which is related to the increase in production of electric vehicles (“EVs”) and hybrid electric vehicles (“HEVs”) as alternatives to traditional internal combustion engine vehicles (“ICEVs”)) and in the fields of electronics and stationary storage systems, all of which will require the production of batteries with excellent electrochemical performance.

[0005] Specifically, global demand for lithium-ion batteries is projected to rise from 0.5 TWh in 2022 to over 2.8 TWh in 2030 (https: / / about.bnef.com / blog / utilities-want-more-energy-storage-but-supply-remains-low / – BloombergNEF. May 26, 2022), with the main contribution coming from transportation electrification (1.745 TWh). Consequently, there will be significant growth in demand for the raw materials needed to produce these batteries, such as graphite, lithium (Li), nickel (Ni), cobalt (Co), lead (Pb), manganese (Mn), aluminum (Al), and copper (Cu).

[0006] Therefore, the development of innovative recycling technologies is crucial to buffering the continued growth of spent lithium-ion batteries, especially in the electric vehicle (EV) sector: the amount of spent lithium-ion batteries is projected to reach 1 Mton / y (0.1 TWh / y) by 2030 and 10 Mton / y (1.3 TWh / y) by 2040, while the current recycling capacity is only 180 kton / y (Source: IEA - International Energy Agency, “The role of critical minerals in clean energy transition” (2022), “World Energy Outlook”).

[0007] Given the scarcity of certain resources defined as “critical materials” (particularly lithium (Li) and cobalt (Co), the fact that their natural reserves will be insufficient to meet the growing demand required for the energy transition appears even more concerning, as reported by Pinegar H. et al. in the Journal of Sustainable Metallurgy (2019), Vol. 5, pp. 402-416, and by the IEA (International Energy Agency) in the Critical Minerals Market Review (2023).

[0008] From a regulatory perspective, lithium-ion batteries used in electric vehicles (“EVS”) are regulated by the General Vehicles Directives 2000 / 53 / EC and 2006 / 66 / EC. On December 9, 2022, the European Union, represented by the European Commission, the European Parliament, and the European Council, reached an agreement on new European regulations for lithium-ion batteries and their recycling, which were published on June 14, 2023 (https: / / www.consilium.europa.eu / it / press / press-releases / 2023 / 07 / 10 / council-adopts-new-regulation-on-batteries-and-waste-batteries / ). The purpose of this document is to promote technological advancements in the battery sector while minimizing environmental impact. A key advantage is the issuance of a “battery passport” by suppliers. In fact, any type of battery (portable, ignition-based, electric vehicle, or industrial vehicle) must be sold with appropriate documentation describing its entire lifecycle. This document will contain information about raw materials (from extraction to production), design, labeling, traceability, collection, recycling, and reuse methods. These products must undergo electronic registration to ensure compliance with the new regulations' safety and traceability requirements. The "battery passport" will be a digital document containing information such as the battery manufacturer, production and market launch dates, battery type and a serial number that reliably identifies the battery, the source of raw materials, hazardous substances contained in the battery, recycled raw materials contained in the battery, and any recycling and recovery processes the battery undergoes at the end of its life (this is the case for secondary batteries). In fact, the new directive offers a significant advantage by providing prior and definitive knowledge of the chemical composition of the cathode, anode, and electrolyte solution, thus encouraging initial sorting before the recycling and recovery processes. Of particular concern among the measures described are the minimum acceptable levels of recycled materials used in the new batteries: 16% cobalt (Co), 85% lead (Pb), 6% lithium (Li), and 6% nickel (Ni).

[0009] Finally, once the law comes into effect, the requirements for performance, durability, and carbon footprint sustainability will be implemented gradually starting in 2024 (https: / / ec.europa.eu / commission / presscorner / detail / en / ip_22_7588).

[0010] Therefore, the recycling and reuse of spent lithium-ion batteries is receiving increasing attention because it can reduce the price of raw materials and protect countries that are heavily reliant on imports of these minerals from an energy perspective, such as those in Europe. Furthermore, the environmental, social, and health impacts of extracting such critical materials will be significantly reduced.

[0011] Lithium-ion batteries are secondary generators with many advantages: long storage life, high specific energy and energy density, and good cycle performance. The battery consists of four main components: cathode (positive electrode), anode (negative electrode), separator, and electrolyte solution. The cathode is composed of an aluminum current collector and cathode material, which includes an active cathode material, a binder, and optional conductive materials. The anode is composed of a copper current collector and anode material, which includes an active anode material and a binder. The cathode and anode are separated by a separator, i.e., a polymer membrane (e.g., polypropylene (PP), polyethylene (PE), polytetrafluoroethylene (PTFE), or mixtures thereof), which prevents possible contact and therefore short circuits. The cathode and anode, along with the separator, are placed in a housing pre-filled with electrolyte solution, and then everything is sealed. The active cathode material is typically composed of a lithium-containing transition metal oxide, such as LiCoO2 (LCO) or LiNi. x Mn y Co zO2 (NMC), where 0 ≤ x, y, z ≤ 1 and x + y + z = 1, LiMn2O4 (LMO), LiFePO4 (LFP), etc. Typically, a small amount of conductive material (e.g., carbon black) and a binder (usually polyvinylidene fluoride PVDF or polytetrafluoroethylene (PTFE)) are added to the oxide to allow the active cathode material to adhere to the current collector. Conversely, the active anode material is typically composed of lithium-ionized graphite, to which a binder (usually carboxymethyl cellulose (CMC)) is added to allow the active anode material to adhere to the current collector. The different components of the battery are divided by weight percentage (w / w %): plastic or steel casing (25%), active cathode material (27%), active anode material (17%), current collector (i.e., aluminum foil and copper foil) (13%), electrolyte solution (usually composed of a solution of LiPF6, LiBF4, LiClO4, LiSo2 dissolved in dimethyl carbonate, propylene carbonate, ethylene carbonate or dimethyl sulfoxide) (10%), separator (4%), and binder (4%) (e.g., reported by Velasquez-Martinez O. et al. in “Batteries” (2019), 5, 68, doi:10.3390 / batteries5040068).

[0012] The working mechanism of lithium-ion batteries is based on the insertion of lithium (Li): in fact, both the anode and cathode are composed of lithium ions that can be inserted into the cathode. + The structure through which lithium ions (Li) pass is composed of positive lithium ions. + Lithium ions (Li) can diffuse in the electrolyte solution. For this reason, positive lithium ions (Li) are released during discharge. + It is inserted from the anode into the cathode, and vice versa during charging.

[0013] Several technologies have been developed to recycle raw materials for end-of-life (EOL) lithium-ion batteries.

[0014] The main recycling technologies known to date are processes designed to extract metals, such as pyrometallurgical processes and hydrometallurgical processes, as well as "direct recycling".

[0015] In pyrometallurgical processes, lithium-ion batteries can be directly subjected to the aforementioned process, or they can first undergo mechanical treatment to obtain the so-called "black substance" before proceeding with the process. Pyrometallurgical processes typically consist of pyrolysis, with an initial temperature of 150°C to 500°C, during which electrolyte compounds and organic solvents are removed. Then, in the presence of chemical reagents (e.g., graphite, coke, NaHSO4, CaCl2, or NH4Cl), a high-temperature treatment up to 1450°C is carried out in a furnace to produce metal alloys containing key metals (e.g., cobalt (Co), copper (Cu), and nickel (Ni)). These alloys can be subjected to separation and purification processes to recover the metals separately. In contrast, lithium (Li), manganese (Mn), and aluminum (Al) ultimately end up in the slag and are therefore unrecoverable. Pyrometallurgical processes are a mature technology, but they are energy-intensive because they are carried out at high temperatures, and they are environmentally harmful because they produce toxic gases that require adequate emission reduction systems, impacting plant and process costs. Furthermore, they do not allow for the recovery of lithium (Li), which can only be recovered through additional expensive processes (e.g., as reported by Doose S. et al. in “Metals” (2021), 11, 291, doi.org / 10.3390 / met11020291).

[0016] Hydrometallurgical processes are widely used to recover cathode metals and lithium through leaching. Mechanical pretreatment is necessary before this process to obtain what is known as "black matter." After separating impurities such as copper, aluminum, and plastics, the metal-enriched phase (primarily rich in Li, Co, Ni, and Mn) typically undergoes the following stages:

[0017] 1) The cathode and anode metals are dissolved by leaching in the presence of strong inorganic acids (e.g., sulfuric acid, hydrochloric acid, nitric acid) and reducing agents (e.g., hydrogen peroxide);

[0018] 2) Purify the leaching solution by chemical precipitation or solvent extraction to remove impurities (e.g., Fe(III), Cu(II), Al) and selectively recover valuable metals (e.g., Co, Ni, Mn, Li).

[0019] Chemical precipitation allows for the selective recovery of metals by altering the pH through the addition of a suitable alkali or by promoting the formation of complexes through the addition of specific binders. Solvent extraction, depending on the solvent used, allows for the selective extraction of metal compounds, which can then be separated by precipitation or distillation. For example, lithium can be recovered as Li₂CO₃ by extraction with supercritical CO₂, which constitutes the extraction solvent.

[0020] In China and South Korea, the aforementioned hydrometallurgical process has been used in several large-scale plants. Further details about the hydrometallurgical process can be found, for example, in Gaines L. et al., “Recycling” (2021) 6, 31, doi.org / 10.3390 / recycling6020031; and Duan X. et al., “Energies” (2022), 15, 1611, doi.org / 10.3390 / en15051611. The hydrometallurgical process is carried out at low temperatures, resulting in low energy consumption, but it consumes a high amount of chemical reagents and requires the treatment of acidic waste.

[0021] It is also known that many studies have been conducted on hydrometallurgical processes with the aim of making the processes more sustainable.

[0022] For example, strong inorganic acids initially used in hydrometallurgical processes can be replaced by organic acids, such as citric acid (as reported by Li L. et al. in the Journal of Hazardous Materials (2010), Vol. 176, Nos. 1-3, pp. 288-293), or by tartaric acid or malic acid, which are typically used in conjunction with reducing agents such as glucose or ascorbic acid. These organic acids can also be produced in situ by microorganisms such as Aspergillus niger (bioleaching).

[0023] Recently, direct recycling processes have become increasingly important, defining a mechanism for recovering materials that make up a battery by separating individual components. The aim is to recover cathode and / or anode materials by restoring their chemical and crystalline structures, allowing them to be used directly in new batteries.

[0024] Generally, direct recycling processes involve disassembling the end-of-life battery after discharge, manually separating the electrodes (i.e., cathode and anode) to prevent the formation of impurities (e.g., iron, copper, and aluminum) during shredding and sieving, followed by processing to remove the electrolyte, which can then be recycled. Primarily, electrolyte removal can be accomplished by extraction with supercritical carbon dioxide (CO2) (as described, for example, in Sloop S. et al., “Sustainable Materials and Technologies” (2020), Vol. 25, e00152). The cathode, after electrolyte removal, consists of a current collector, typically an aluminum foil with a thickness of approximately 0.1 mm, coated with a cathode material comprising an active cathode material, optional conductive material (e.g., acetylene black, carbon black), and an organic binder [e.g., polyvinylidene fluoride (PVDF)]. One challenge of the aforementioned direct recycling process is separating the cathode material from the current collector, particularly due to the presence of the organic binder [e.g., polyvinylidene fluoride (PVDF)]. To this end, key technologies include the thermal decomposition of organic binders [e.g., polyvinylidene fluoride (PVDF)] or their dissolution in organic solvents. Compared to pyrometallurgical and hydrometallurgical processes, direct recycling processes have lower technological maturity, requiring pre-classification of batteries with the same chemical composition (LCO, NMC, LMO, NCA, or LFP) and regeneration of the active cathode material, compensating for lithium loss during battery use through relithiation.

[0025] Generally, the recycling process of lithium-ion batteries involves a series of preparatory steps, such as:

[0026] - Battery classification: Select the battery to be processed based on the different chemical compositions of the cathode electrode material and the anode electrode material, as well as their size and structure (e.g., cylindrical, prismatic, or pouch).

[0027] - Battery Discharge: Any residual charge in spent batteries during recycling can lead to short circuits, overheating, and consequently, flames; proper discharge allows for safe operation and can be achieved through: immersion in a brine solution (e.g., an aqueous solution of sodium chloride, ferric sulfate, or manganese sulfate); cryogenic deactivation (e.g., treatment in liquid nitrogen at temperatures ranging from -175°C to -200°C, a typical practice for companies such as Umicore, Toxco, and Eco Recycling); thermal deactivation (e.g., evaporation of the electrolyte solution under vacuum treatment up to 250°C, a typical practice for Accurec); or ohmic discharge using a controlled current discharge via an electronic load.

[0028] - Battery disassembly: Separating different components, including electrodes (i.e., anode and cathode), separator, casing, and battery management system (BMS);

[0029] - Pretreatment aims to make the active electrode materials (both cathode and anode) more accessible by separating them from their respective current collectors (copper for anode and aluminum for cathode) and the diaphragm. Pretreatment is mainly carried out by mechanical, thermal or chemical means.

[0030] - As mentioned above, metals are recovered through pyrometallurgical processes, hydrometallurgical processes, and direct recycling processes.

[0031] More information on the above treatments can be found, for example, in Zheng Z. et al., “Engineering” (2018), Vol. 4, pp. 361-370; Harper G. et al., “Nature” (2019), Vol. 575, pp. 75-86; and Zheng F. et al., “Journal of Cleaner Production” (2022), Vol. 359, 132116, doi.org / 10.1016 / jjclepro.2022.132116.

[0032] Specifically, pretreatment is one of the key factors affecting processes, particularly hydrometallurgical processes and direct recycling processes. The purpose of pretreatment is to remove materials (e.g., plastics, aluminum, copper) that do not directly participate in the subsequent recycling process in order to maximize the extraction efficiency of the metal of interest.

[0033] For example, in order to peel the cathode material from the current collector, the effect of the binder (e.g., polyvinylidene fluoride (PVDF), a chemically very stable fluoropolymer capable of operating at high temperatures (up to 150°C)) must be suppressed. Some specific examples of pretreatments used for the above purposes are reported below:

[0034] - Mechanical pretreatment, which is the most common and industrially implemented, involves the battery undergoing crushing and physical separation processes utilizing certain properties (e.g., particle size, density, ferromagnetism, hydrophobicity) after disassembly. This pretreatment may include, for example, magnetic shell separation, separation of non-magnetic components (e.g., aluminum, copper) from plastics, screening, eddy current use, and flotation, with the aim of obtaining so-called "black matter," which comprises enriched powders of active cathode and / or active anode materials, which are subsequently recycled using various recycling technologies.

[0035] - Heat treatment is performed at high temperatures (400°C to 600°C) to suppress the effect of the binder, thereby reducing the adhesion between the electrode material and the current collector; in the case of polyvinylidene fluoride (PVDF), it is decomposed and the CF bond breaks with the formation of hydrofluoric acid (HF); then separation between the cathode material and the current collector is carried out by grinding or flotation.

[0036] - Aluminum current collectors were chemically pretreated for 5 hours at room temperature (25°C) using a 10% (w / w) sodium hydroxide (NaOH) solution to dissolve them, forming NaAlO2 and NaAl(OH)4. While this method requires relatively simple preparation, aluminum is difficult to recover because it exists in ionic form in solution. Alternatively, polyvinylidene fluoride (PVDF) can be dissolved in aprotic solvents such as N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), or N,N-dimethylacetamide (DMAC). However, these solvents have significant permanent dipole moments and are not readily used as proton donors, limiting their reactivity (e.g., reported by Marshall JE et al. in "Polymers" (2021), 13, 1354, doi.org / 10.3390 / polym13091354). The effectiveness of these solvents can be improved by using ultrasound (e.g., He LP et al. in "Waste Management" (2015)). (This is reported in Volume 46, pages 523-528).

[0037] In chemical pretreatment, one class of potentially effective compounds is diols.

[0038] For example, Bay Y. et al., in "ChemSusChem" (2020), Vol. 13, pp. 5664-5670, describe the use of pure ethylene glycol without any additives to effectively separate cathode materials from the corresponding aluminum (Al) current collectors for a direct recycling process. According to the authors, ethylene glycol is able to counteract the binder effect through a competitive inhibition mechanism of hydrogen bonding. Specifically, due to the formation of hydrogen bonds between polyvinylidene fluoride (PVDF) and the aluminum oxide (Al2Or3) of the current collector, ethylene glycol will "weaken" the binder by promoting the separation of the cathode material (specifically, active cathode materials based on nickel, manganese, and carbon (NMC)) from the current collector itself and establishing hydrogen bonds.

[0039] Patent application US 2021 / 0257685 relates to a method for recycling lithium-ion batteries, comprising:

[0040] (a) Separating a composite electrode from a spent lithium-ion battery, the composite electrode comprising an electrode material bonded to a current collector using polyvinylidene fluoride (PVDF) as an adhesive;

[0041] (b) The composite electrode is brought into contact with at least one fluid polyol capable of releasing polyvinylidene fluoride (PVDF) from the current collector, thereby forming a mixture;

[0042] (c) Stripping the electrode material from the current collector to obtain free electrode material and free current collector;

[0043] (d) Recover the free electrode material and the free current collector.

[0044] The fluid polyol can be a glycol, glycerol, or a mixture thereof. In the case of ethylene glycol, it has been reported that the electrode material completely decouples from the current collector within 2 to 120 seconds at temperatures ranging from 160°C to 198°C. This method is said to preserve the morphology of the electrode material, allowing it to be reused in lithium-ion batteries.

[0045] Rose S. et al., in "Advanced Energy & Sustainability Research" (2021), 2, 2100040, doi:10.1001 / aesr.202100040, described the use of ethylene glycol as an alternative to N-methyl-2-pyrrolidone (NMP) in the pretreatment of the leaching process. Specifically, under the same operating conditions, the authors noted that the efficiency of metal recovery increased when ethylene glycol was used instead of NMP for pretreatment. The authors believe that ethylene glycol is a reducing agent, exhibiting partial reduction of the metal even in the pretreatment step, thereby improving the subsequent leaching process.

[0046] Gu K. et al. described a hot glycerol stripping process in the "Journal of Cleaner Production" (2022), 369, 133270, doi.org / 10.1016 / j.clepro.2022.133270. Specifically, the authors investigated the effects of different experimental parameters (i.e., processing time, temperature, and mixing rate) on the stripping efficiency of cathode materials (specifically, nickel-manganese-cobalt (NMC) based active cathode materials). The optimal process conditions were: a target temperature of 200 °C, a mixing rate of 350 r / min, and a processing time of 15 min.

[0047] However, particularly from an industrial application perspective, this pretreatment can present challenges, partly due to the hazards of the reagents used and / or the reaction products they generate. For example:

[0048] - The dissolution of cathode material in sodium hydroxide (NaOH) may cause eye irritation and skin burns (Hazard Statement H314); in addition, the pretreatment results in complex management of alkaline wastewater, which is particularly harmful to the environment, and since one of the main reaction products is hydrogen, care must be taken to avoid explosion;

[0049] Polyvinylidene fluoride (PVDF) dissolved in aprotic solvents (e.g., N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAC), which are particularly toxic agents) can cause environmental and operational problems; in fact, DMF, NMP, and DMAC all have hazard statements H360D, indicating potential fetal toxicity; furthermore, in the cases of DMF and DMAC, additional warnings can be identified, such as hazard statements H312+H332 (toxic if inhaled or exposed to skin) or H319 (eye irritation), while NMP may cause respiratory irritation (hazard statement H335).

[0050] - To suppress the effect of polyvinylidene fluoride (PVDF), heat treatment is performed at high temperatures (i.e., 500°C to 600°C), resulting in the evaporation and decomposition of PVDF and electrolyte salts (e.g., LiPF6 or LiBF4), thereby forming hydrofluoric acid (HF) in gaseous form; for this reason, specific emission reduction systems for the gas are necessary, as ingestion (hazard statement H300), skin contact (hazard statement H310), or inhalation (hazard statement H330) of the gas is fatal; other potentially harmful substances produced include dioxins, lithium fluoride (LiF), cobalt difluoride (CoF2), and carbon monoxide (CO); furthermore, at temperatures above 600°C, the aluminum foil becomes brittle, making it difficult to peel the cathode material from the current collector.

[0051] Other concerns may relate to the types of reagents used in hydrometallurgical processes to extract key metals: in fact, a typical pair of reagents used in hydrometallurgical processes are sulfuric acid (H2SO4) as a leaching agent and hydrogen peroxide (H2O2) as a reducing agent.

[0052] To overcome these concerns, research has been conducted on using organic acids (e.g., citric acid, malic acid, tartaric acid, oxalic acid) as alternatives to commonly used inorganic acids (e.g., sulfuric acid (H₂SO₄), hydrochloric acid (HCl), nitric acid (HNO₃)) to avoid harmful gases (e.g., SO₂). x NO x ,ClO xThe formation of ) (e.g., reported by Meshram p. et al. in "Chemosphere" (2020), 242, 125291, doi.org / 10.1016 / J.chemosphere.2019.125291).

[0053] Further research has been conducted on the use of ethylene glycol, a green alternative, reducing agent, and substitute for hydrogen peroxide (H2O2), a substance harmful when ingested (H3O2 hazard statement) or inhaled (H332 hazard statement), causing skin burns and eye damage (H314 hazard statement), as reported by Zeng G. et al. in "ACS Sustainable Chemistry & Engineering" (2021), Vol. 9, pp. 16133-16142. These authors reported using a solution of ethylene glycol and citric acid (EG-CA) to separate cathode material from the current collector, utilizing the resulting ester as a corrosion inhibitor.

[0054] However, significant challenges remain in the initial separation of cathode materials from current collectors in order to recover reusable components from current collectors in a cost-effective and environmentally friendly manner.

[0055] Therefore, the applicant set out to address the problem of finding new methods for recovering cathode materials from lithium-ion batteries.

[0056] The applicant has now discovered a method for recovering cathode material from lithium-ion batteries, the method being carried out under specific power, temperature, and time conditions in the presence of at least one diol and ultrasound. This method allows for the efficient recovery of cathode material from the current collector while operating at temperatures below the binder decomposition temperature, reducing the risk of toxic gases generated by the decomposition of binders or electrolyte salts. Furthermore, this method allows for the acquisition of cathode material through which, after appropriate treatment, recovered active cathode material can be obtained (e.g., via a direct recycling process), or synthetic precursors that can be used to regenerate said active cathode material (e.g., via a hydrometallurgical process), which can then be used in lithium-ion batteries.

[0057] Furthermore, the use of diols has many advantages compared to other reagents used in pretreatment because they are green, ecological, biodegradable, economical, readily available, and recyclable.

[0058] Therefore, the object of the present invention is a method for recovering cathode material from lithium-ion batteries, comprising the following stages:

[0059] (a) Separating the cathode from the lithium-ion battery, the cathode comprising a cathode material and a current collector, the cathode material comprising at least one active cathode material, at least one adhesive and optionally at least one conductive material, the cathode material being adhered to the current collector by the at least one adhesive;

[0060] (b) Contact the cathode with at least one diol;

[0061] (c) Stripping the cathode material from the current collector to obtain a mixture comprising a suspension of the cathode material dispersed in a liquid phase comprising at least one diol and a current collector immersed in the suspension;

[0062] (d) Recover the cathode material and the current collector from the mixture;

[0063] The characteristic feature is that the stage (c) is performed in the presence of ultrasound with a power of 30 watts to 500 watts, preferably 50 watts to 300 watts, at a temperature of 80 to 280°C, preferably 85 to 260°C, for a duration of 15 minutes to 24 hours, preferably 30 minutes to 20 hours.

[0064] For the purposes of this specification and the foregoing claims, the definition of a numerical range always includes extreme values, unless otherwise stated.

[0065] For the purposes of this specification and the foregoing claims, the term "comprising" also includes the terms "consistently composed of" or "composed of".

[0066] The method according to the invention is applicable to all types of lithium-ion batteries, regardless of their internal chemical composition and the physical dimensions of the battery itself.

[0067] According to a preferred embodiment of the present invention, the active cathode material comprises at least one lithium-containing metal oxide, which may be selected from, for example:

[0068] - Lithium manganese oxide (LMO), lithium nickel oxide (LNO), lithium cobalt oxide (LCO), lithium iron phosphate (LFP), or mixtures thereof;

[0069] - A mixed oxide of lithium, manganese, cobalt, nickel, and aluminum, preferably selected from those having the following general formula: LiNi x Mn y O2, Li 1+z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z O2, LiNi x Coy Mn z O2, where each of x, y, and z is typically a mole fraction of 0 to 1, where x + y + z = 1, or a mixture thereof;

[0070] Or a mixture thereof.

[0071] According to a preferred embodiment of the invention, the adhesive may be selected from, for example: polyvinylidene fluoride (PVDF) homopolymer, copolymers or interpolymers of polyvinylidene fluoride (PVDF) with one or more other monomers, polytetrafluoroethylene, fluorinated ethylene-propylene copolymers (e.g., tetrafluoroethylene and / or hexafluoropropylene), perfluoroalkoxy polymers or polyfluoroalkoxy polymers or mixtures thereof; preferably polyvinylidene fluoride (PVDF) homopolymer.

[0072] To improve the electronic conductivity of the cathode material, the cathode material may optionally contain a conductive material.

[0073] According to another preferred embodiment of the present invention, the conductive material may be selected from, for example, acetylene black, carbon black, preferably carbon black.

[0074] For the purposes of this invention, the current collector can be any form known in the art, such as a sheet or foil. The current collector can have any thickness suitable for current transmission, but a minimum thickness will generally be chosen to maximize energy density.

[0075] According to a preferred embodiment of the present invention, the current collector is aluminum foil.

[0076] The stage (a) of separating the cathode from the lithium-ion battery can be performed by methods known in the art. For example, the method typically includes discharging the lithium-ion battery before further processing, i.e., removing any residual charge stored in the battery. Preferably, the lithium-ion battery is fully discharged before undergoing this stage (a).

[0077] Lithium-ion batteries can be discharged using techniques known in the art, for example, by immersing the battery in an aqueous solution (e.g., neutral or alkaline) containing a conductive salt (e.g., NaHCO3, KHCO3, Na2CO3, K2CO3, CaCO3, MgCO3, NaOH, KOH, Ca(OH)2, Mg(OH)2, NaCl, CaCl2, etc., or mixtures thereof). Alternatively, the discharge of the lithium-ion battery can be performed using an electronic load for controlled current discharge.

[0078] In some implementations, the casing of the lithium-ion battery may be drilled (e.g., by piercing, cutting, etc.) before the lithium-ion battery is immersed in an aqueous solution for discharge. Typically, battery discharge is carried out at a temperature not exceeding 60°C.

[0079] After a lithium-ion battery is discharged, separating the electrodes (cathode and anode) typically involves removing the battery and separating the electrodes (cathode and anode) from other battery components such as the separator, casing, electrolyte, and battery management system (BMS).

[0080] The separation process can be carried out in different ways using any techniques known in the art. For example, the purpose of selecting a separation technique is usually to avoid damaging or destroying the electrode or rendering it less usable than before separation.

[0081] In some implementations, spent lithium-ion batteries can be shredded, cut, or ground into smaller fragments (e.g., by manual or computer-monitored sawing / blade cutting, water jet cutting, etc.). The resulting components can be sized to suit uniformity, larger surface area, and the processing capacity of the specific equipment used.

[0082] In some embodiments, the electrode separation process further includes cleaning the electrodes. In these embodiments, the electrodes are typically cleaned with an organic solvent that does not react with the electrodes, and it is also possible to remove any residual electrolyte from the electrodes.

[0083] According to a preferred embodiment of the invention, prior to stage (b), the cathode may be cleaned in an ultrasonic bath at room temperature (25°C) with an organic solvent (e.g., acetone, dimethyl carbonate, 2-butanone, preferably acetone) for 10 minutes to 2 hours, preferably 20 minutes to 1 hour.

[0084] Preferably, the minimum power of the ultrasonic bath is 50 watts to 100 watts.

[0085] After cleaning, the cathode is dried to remove any trace solvent. Preferably, drying can be carried out at a temperature of 50°C to 130°C, more preferably 70°C to 120°C, for 1 hour to 5 hours, more preferably 1.5 hours to 4 hours.

[0086] According to a preferred embodiment of the present invention, the diol may be selected from, for example: ethylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, glycerol, or mixtures thereof; preferably 1,3-propanediol or 1,2-propanediol.

[0087] According to a preferred embodiment of the invention, stage (b) can be carried out at a cathode / diol weight ratio of 1:5 to 1:150, preferably 1:10 to 1:140.

[0088] According to a preferred embodiment of the invention, in stage (b), the diol can be heated to a temperature of 80°C to 280°C, preferably 85°C to 260°C, before contacting the cathode.

[0089] According to a preferred embodiment of the invention, in stage (c), ultrasound can be applied at different time intervals, preferably for a duration of 5 to 60 seconds, preferably 10 to 40 seconds, with a time interval of 5 to 60 minutes, preferably 8 to 40 minutes.

[0090] The mixture obtained in stage (c) comprises a suspension of cathode material dispersed in a liquid phase containing glycol and a current collector (i.e., aluminum foil) immersed in the suspension. As shown below, in stages (d2) and optionally (d3), any cathode material that remains adhered to the current collector can be recovered.

[0091] According to a preferred embodiment of the present invention, stage (d) includes the following stages:

[0092] (d1) Cool the mixture obtained in stage (c) to room temperature (25°C) and sieve it to obtain:

[0093] (i) a suspension of cathode material dispersed in a liquid phase containing diol; and

[0094] (ii) A clean or partially clean current collector; and

[0095] The suspension of cathode material dispersed in a liquid phase containing diol is vacuum filtered, and the obtained filtrate is washed with at least one organic solvent selected from, for example, acetone, dimethyl carbonate, 2-butanone, preferably acetone, to obtain a first cathode material. The first cathode material is preferably dried in an oven at a temperature of 50°C to 130°C, preferably 70°C to 120°C, for a period of 1 hour to 5 hours, preferably 1.5 hours to 4 hours.

[0096] (d2) In the presence of at least one organic solvent selected from, for example, acetone, dimethyl carbonate, 2-butanone, preferably acetone, the current collector obtained in stage (d1) is immersed in an ultrasonic bath to obtain a second cathode material and a clean or partially clean current collector. The second cathode material is recovered by vacuum filtration and preferably dried in an oven at a temperature of 50°C to 130°C, preferably 70°C to 120°C, for 1 hour to 5 hours, preferably 1.5 hours to 4 hours.

[0097] (d3) Optionally, the current collector recovered in the treatment stage (d2) is placed in an organic solvent selected from, for example, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, dipropylene glycol, preferably dipropylene glycol, at a temperature of 100°C to 250°C, preferably 120°C to 245°C, for 30 minutes to 5 hours, preferably 1 hour to 4 hours, to obtain a third cathode material and a clean current collector. The third cathode material is then recovered by vacuum filtration and preferably dried in an oven at a temperature of 50°C to 130°C, preferably 70°C to 120°C, for 1.5 to 5 hours, preferably 2 hours to 4 hours.

[0098] For the purposes of this specification and the foregoing claims, "clean or partially clean current collector" refers to a current collector that does not contain residual cathode material or a current collector in which residual cathode material is present.

[0099] Preferably, in stage (d2), the minimum power of the ultrasonic bath is 50 watts to 100 watts.

[0100] At the end of stage (d), the first cathode material recovered in stage (d1) and the second cathode material recovered in stage (d2) are combined and analyzed as follows. However, any third cathode material recovered in stage (d3) is only considered for yield calculation.

[0101] As described above, from the cathode material recovered by the above method, after appropriate treatment, recovered active cathode material can be obtained (e.g., through a direct recycling process), or synthetic precursors that can be used to regenerate the active cathode material can be obtained (e.g., through a hydrometallurgical process), which can then be used in lithium-ion batteries.

[0102] To better understand and put the invention into practice, some illustrative and non-limiting embodiments are reported below.

[0103] Use the analytical and characterization methods reported below.

[0104] X-ray diffraction

[0105] Therefore, the cathode material sample (approximately 1.5 g) obtained in the examples reported below was analyzed using a D5000 X-ray powder diffraction (XRD) system (Siemens): the obtained spectra were examined using diffract.suite EVA software and the crystal structure was identified using the PDF-2 Release 2019 RDB database.

[0106] For comparison, any changes in the crystal structure of the starting cathode material were also analyzed. To this end, a starting cathode sample was prepared by removing approximately 1.5 g of surface cathode material with a scraper, taking care to avoid contamination by the aluminum current collector.

[0107] Scanning electron microscope (SEM)

[0108] Therefore, the cathode material sample (approximately 0.5 g) obtained in the examples reported below was analyzed by scanning electron microscopy (SEM) using a FESEM Inspect F50 (Thermofisher) instrument.

[0109] For comparison, any changes in the crystal structure of the cathode material in the starting cathode were also analyzed. For this purpose, a starting cathode sample with dimensions of 1.5 × 1.5 cm was prepared.

[0110] Attenuated Total Reflectance (ATR) Infrared Spectroscopy

[0111] To verify the properties of the adhesive, a sample taken from the initial cathode of Example 1 was examined through a lens with a resolution of 2 cm. -1 Characterization was performed using a Perkin Elmer Spectrum One FT-IR spectrophotometer equipped with an ATR diamond / ZnSe attachment. When a compound is indicated to have a peak in its infrared spectrum at a given value, this typically means that the peak is within ±2 cm⁻¹. -1 between.

[0112] The above sample was obtained by immersing the starting cathode in N,N-dimethylformamide at 140°C for 2.5 hours. Subsequently, the obtained solution was cooled to room temperature (25°C) and vacuum filtered to obtain the filtrate, which was then concentrated to obtain the binder, and the binder was subjected to spectral analysis using the above-mentioned spectrophotometer.

[0113] For comparison, the standard sample of polyvinylidene fluoride (PVDF) (particle-Aldrich) was analyzed.

[0114] The obtained spectrum is as follows Figure 5 As shown, at 1663 cm -1 and 2929 cm -1 The non-overlapping peaks are associated with N,N-dimethylformamide used to dissolve the cathode binder.

[0115] The most significant peak a for PVDF adhesive is located at 763 cm⁻¹. -1 (-CF2 bending vibration) and 1172 cm -1 (-CF2 symmetric stretching vibration).

[0116] Examples 1-2

[0117] The lithium-ion battery (LG BL-45F1F, Typ 2500mAh / 9.6WHr, Yantai Electronics Inc.) was discharged using the IMAX-B6AC V2 device (charger / discharger). The battery was considered discharged when the cell potential approached 0.

[0118] The battery is then manually disassembled into various components: electrodes (i.e., cathode and anode), separator, casing, electrolyte, and control unit (battery management system - BMS).

[0119] The small amount of electrolyte (several ml) adsorbed on the cathode surface was removed by immersing the cathode in acetone in an ultrasonic bath at room temperature (25°C) for about 30 minutes. The cathode was then separated and dried in an oven at 80°C for 2 hours to remove any trace amounts of acetone.

[0120] The obtained cathode has the following crystal structure: LiMn2O4.

[0121] The cathode of the embodiment is obtained by operating as described above.

[0122] 1,3-Propanediol (Merck) (Example 1) or 1,2-Propanediol (Merck) (Example 2) was placed in a 1-liter three-necked flask equipped with a bubble condenser: the free volume of the flask above the solution was inertized by maintaining a constant flow of nitrogen into the flask and out through the bubble condenser. A heating mantle was applied to the flask (Universal mod. 133) to reach the set point temperature. Subsequently, a bubble condenser cooled using a Huber K20 cooling circulator was applied to the top of the flask to prevent diol evaporation. The temperature inside the flask was monitored using thermocouples, and when the desired temperature was reached (as shown in Table 1), a pre-weighed cathode obtained as described above was added, and ultrasound was applied using a QSONICA Q700 ultrasonic transducer with a power set to 150 watts. Ultrasonic treatment was performed by inserting a probe into the flask from above, almost touching the bottom of the flask, and then returning it upwards, for 30 seconds every 30 minutes, for durations as shown in Table 1.

[0123] At the end of the processing [stage (c)], a mixture is obtained comprising a suspension of the cathode material dispersed in a liquid phase containing at least one of the diols and a partially clean current collector (i.e., aluminum foil) immersed in the suspension.

[0124] The mixture obtained in stage (c) is cooled to room temperature (25°C) and screened to obtain: (i) a suspension of cathode material dispersed in a liquid phase containing diol, and (ii) a partially cleaned current collector (i.e. aluminum foil) [stage (d1)].

[0125] The cathode material suspension obtained in stage (d1) and dispersed in a liquid phase containing diol was vacuum filtered, the obtained filter was washed with acetone (100 ml) (Merck), and dried in an oven at 80°C for 3 hours to obtain the first cathode material [stage (d1)].

[0126] In the presence of acetone (150 ml) (Merck), the current collector (i.e., aluminum foil) obtained in stage (d1) was immersed in an ultrasonic bath for approximately 30 minutes to facilitate the removal of cathode material still adhering to the current collector (i.e., aluminum foil), thereby obtaining a second cathode material and a clean current collector [stage (d2)] (Example 1). The second cathode material was recovered by vacuum filtration and dried in an oven at 80°C for 3 hours to obtain a second cathode material, which was then combined with the first dried cathode material obtained as described above.

[0127] In Example 2, the current collector (i.e., aluminum foil) recovered in stage (d2) was treated with dipropylene glycol (Merck) (200 ml) at 243°C for 2 hours to obtain the third cathode material and a clean current collector (i.e., aluminum foil) [stage (d3)]. The third cathode material was recovered by vacuum filtration and dried in an oven at 80°C for 3 hours to obtain the third cathode material considered in the yield calculation.

[0128] The cathode materials obtained as described above (i.e., from stage (d1) and stage (d2)) and the starting cathode material were analyzed by X-ray diffraction and scanning electron microscopy (SEM) as operated as described above. The data obtained are reported below:

[0129] - Figure 1 XRD spectrum of the starting cathode material;

[0130] - Figure 2 XRD spectrum of the cathode material obtained in Example 1;

[0131] - Figure 3 XRD spectrum of the cathode material obtained in Example 2;

[0132] - Figure 4 :

[0133] - SEM images of the starting cathode materials for Examples 1 and 2, shown on the left and labeled a) and b) respectively;

[0134] - SEM images of the cathode materials obtained in Examples 1 and 2, shown on the right and labeled c) and d) respectively.

[0135] Figure 1-3The presence of two main phases in the recovered cathode material, LiMn2O4 and Mn3O4, supports the fact that a portion of the starting material remains unchanged, while a certain percentage of the starting material has been converted into manganese oxide (Mn3O4), i.e., transformed into one of the main degradation products through the distortion of the crystal structure and the loss of lithium in the structure.

[0136] Figure 4 The cathode material particles show no morphological change due to the effect of the diol. Furthermore, it can be observed that in the initial cathode material, the binder is uniformly deposited at the surface level [SEM images shown on the left and indicated by letters a) and b)], however, as a result of heat treatment and the corresponding phase transition, it tends to concentrate in certain areas [SEM image shown on the right and indicated by letter d)], while leaving other areas depleted [SEM image shown on the right and indicated by letter c)].

[0137] Table 1 shows, in sequence: Example No. (Example), Diol used (diol), Time in hours (h) and Temperature in degrees Celsius (°C) (Experimental conditions), Amount of diol used in grams [Diol weight (g)], Initial weight of cathode in grams (i.e., weight of starting cathode) (Initial foil weight TQ (g)), Cathode / diol ratio (i.e., starting cathode) (Ratio g / g), Weight of current collector obtained in [Stage (d2)] in grams (i.e., weight of aluminum foil) [Al foil weight] 1 (g)], the weight of the current collector obtained in [stage (d3)] in grams (i.e., the weight of the aluminum foil) [Al foil weight] 2 (g) The yield expressed as a percentage [Yield (%)] calculated according to the following formula:

[0138]

[0139] in:

[0140] - Total net weight of cathode material = Initial weight of current collector TQ - Weight of current collector after stage (d3)

[0141] - Net weight of cathode material = weight of current collector after stage (d2) - weight of current collector after stage (d3).

[0142] exist Figure 6 and Figure 7 In (Example = Example), the recycled current collector (i.e., aluminum foil) is shown: it can be seen that the foil is clean.

[0143] Table 1

[0144]

[0145] *: Stage (d3) was not performed because the current collector (i.e., aluminum foil) was found to be clean and the yield was considered to be 100%.

Claims

1. A method for recovering cathode material from a lithium-ion battery, comprising the following stages: (a) Separating the cathode from the lithium-ion battery, the cathode comprising a cathode material and a current collector, the cathode material comprising at least one active cathode material, at least one adhesive and optionally at least one conductive material, the cathode material being adhered to the current collector by the at least one adhesive; (b) Contact the cathode with at least one diol; (c) Stripping the cathode material from the current collector to obtain a mixture comprising a suspension of the cathode material dispersed in a liquid phase comprising at least one diol and a current collector immersed in the suspension; (d) Recover the cathode material and the current collector from the mixture; The characteristic feature is that the stage (c) is performed in the presence of ultrasound with a power of 30 watts to 500 watts, preferably 50 watts to 300 watts, at a temperature of 80 to 280°C, preferably 85 to 260°C, for a duration of 15 minutes to 24 hours, preferably 30 minutes to 20 hours.

2. The method for recovering cathode material from a lithium-ion battery according to claim 1, wherein the active cathode material comprises at least one lithium-containing metal oxide selected from: - Lithium manganese oxide (LMO), lithium nickel oxide (LNO), lithium cobalt oxide (LCO), lithium iron phosphate (LFP), or mixtures thereof; - A mixed oxide of lithium, manganese, cobalt, nickel, and aluminum, preferably selected from those having the following general formula: LiNi x Mn y O2, Li 1+ z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z O2, LiNi x Co y Mn z O2, where each of x, y, and z is typically a mole fraction of 0 to 1, where x + y + z = 1, or a mixture thereof; Or a mixture thereof.

3. The method for recovering cathode material from a lithium-ion battery according to claim 1 or 2, wherein the binder is selected from: polyvinylidene fluoride (PVDF) homopolymer, copolymers or interpolymers of polyvinylidene fluoride (PVDF) with one or more other monomers, polytetrafluoroethylene, fluorinated ethylene-propylene copolymers (e.g., tetrafluoroethylene and / or hexafluoropropylene), perfluoroalkoxy polymers or polyfluoroalkoxy polymers or mixtures thereof; preferably polyvinylidene fluoride (PVDF) homopolymer.

4. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein the conductive material is selected from acetylene black, carbon black, and preferably carbon black.

5. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein the current collector is aluminum foil.

6. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein, prior to stage (b), the cathode is cleaned in an ultrasonic bath at room temperature (25°C) with an organic solvent such as acetone, dimethyl carbonate, 2-butanone, preferably acetone, for 10 minutes to 2 hours, preferably 20 minutes to 1 hour.

7. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein the diol is selected from: ethylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, glycerol, or mixtures thereof; preferably 1,3-propanediol or 1,2-propanediol.

8. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein stage (b) is carried out at a cathode / diol weight ratio of 1:5 to 1:150, preferably 1:10 to 1:

140.

9. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein in stage (b), the diol is heated to a temperature of 80°C to 280°C, preferably 85°C to 260°C, before contacting the cathode.

10. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein in stage (c), ultrasonic waves are applied at different time intervals, preferably for a duration of 5 to 60 seconds, preferably 10 to 40 seconds, with the time interval being 5 to 60 minutes, preferably 8 to 40 minutes.

11. A method for recovering cathode material from a lithium-ion battery according to any one of the preceding claims, wherein stage (d) comprises the following stages: (d1) Cool the mixture obtained in stage (c) to room temperature (25°C) and sieve it to obtain: (i) A suspension of the cathode material dispersed in a liquid phase containing diol; as well as (ii) Clean or partially clean current collectors; and The suspension of the cathode material dispersed in a liquid phase containing diol is vacuum filtered, and the obtained filtrate is washed with at least one organic solvent selected from acetone, dimethyl carbonate, 2-butanone, preferably acetone, to obtain the first cathode material. Preferably, the first cathode material is dried in an oven at a temperature of 50°C to 130°C, preferably 70°C to 120°C, for 1 hour to 5 hours, preferably 1.5 hours to 4 hours. (d2) In the presence of at least one organic solvent selected from acetone, dimethyl carbonate, 2-butanone, preferably acetone, the current collector obtained in stage (d1) is immersed in an ultrasonic bath to obtain a second cathode material and a clean or partially clean current collector. The second cathode material is recovered by vacuum filtration and preferably dried in an oven at a temperature of 50°C to 130°C, preferably 70°C to 120°C, for 1 hour to 5 hours, preferably 1.5 hours to 4 hours. (d3) Optionally, the current collector recovered in the treatment stage (d2) is placed in an organic solvent selected from N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, dipropylene glycol, preferably dipropylene glycol, at a temperature of 100°C to 250°C, preferably 120°C to 245°C, for 30 minutes to 5 hours, preferably 1 hour to 4 hours, to obtain a third cathode material and a clean current collector. The third cathode material is then recovered by vacuum filtration and preferably dried in an oven at a temperature of 50°C to 130°C, preferably 70°C to 120°C, for 1.5 to 5 hours, preferably 2 hours to 4 hours.

Citation Information

Patent Citations

  • Efficient recovery processes for the black mass from spent lithium-ion batteries

    US20210257685A1